KOSAKATA DALAM TRADISI NGAMPING MASYARAKAT MELAYU DESA RAMBAYAN KABUPATEN SAMBAS - Eni, Eni; Patriantoro, Patriantoro; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Language is basically a practical symbol to identify the region and tribe of the speakers. Language becomes a tool for people to communicate with each other in everyday life. One of the regional languages that become the nation's cultural wealth is Sambas Dialect Malay. Sambas Dialect Malay is always used by the community in various activities, one of which is the implementation of the Ngamping tradition. In the current era, many young people are starting to forget their respective regional cultures. Therefore, the researcher wants to inventory the ngamping tradition starting from the form of lingual units, lexical meaning, cultural meaning, and vocabulary function. This research uses descriptive method with qualitative research form. The research data obtained in the form of words and phrases from informants through direct interview techniques with informants related to the location of the object under study, namely Rambayan Village, Sambas Regency. The results of this study amounted to 44 vocabularies which were divided into 31 monomorphemic data, 2 polymorphic data, and 11 phrase data. The data also produced 41 lexical meanings, 3 cultural meanings, and 44 vocabulary functions. The data were obtained based on actors, activity names, place names, cultural names, food names, and names of ingredients and tools.